Industrial renewal and growth through nanotechnology? An overview with focus on Finland - Christopher Palmberg; Tuomo Nikulainen (The Research Institute of the Finnish Economy (ETLA), 2006)
Hardly any other field has received so much public R&D investments globally in such a short time as nanotechnology. Nanotechnology can be considered as an umbrella term for R&D at the nanometer scale (1-100 nm) where unique phenomena enable novel applications. The interest given to nanotechnology is largely due to its perceived, and partly also over-hyped, generic nature and potentials to renew industries in a revolutionary way. Nonetheless, the field is still in a fluid and nascent phase without clear indications of how and where commercial breakthroughs will emerge on a larger scale. This paper aims to conceptualize nanotechnology in the literature on the economics of technological change, review the extant empirical research towards this end, and provide a brief overview and new insights into the development of nanotechnology in Finland. It discusses to what degree nanotechnology fits the criteria of a general purpose technology (GPT) and, in this context, highlights some important issues related to technology transfer, industrial dynamics and organisation. The case of Finland is interesting due to recent and relatively significant nanotechnology policy initiatives and the competitive position that it holds in many traditional industries. Although new firms also are emerging, Finnish nanotechnology primarily appears to be driven by scientific developments and the role of large firms is still small. Patenting is picking up from a low level, and process engineering and chemicals are emerging as the main application fields.
Keywords: O32; O33; O40; 330; nanotechnology; general purpose technology; industrial renewal; Finland; Hochtechnologiesektor; Forschungs- und Technologiepolitik; Finnland; Nanotechnologie